Reversible structural transformation induced switchable single-molecule magnet behavior in lanthanide metal–organic frameworks. Issue 72 (23rd August 2018) - Wang, Mengmeng; Meng, Xixi; Song, Fen; He, Yanfei; Shi, Wei; Gao, Hongling; Tang, Jinkui; Peng, Cheng
Abstract : The structural transformation between Ln-MOFs1 and2 and the corresponding switchable "on/off" single-molecule magnet behavior have been studied. Abstract : Switchable "on/off" single-molecule magnet (SMM) behavior can be realized in lanthanide metal–organic frameworks (Ln-MOFs) tuned by the temperature-induced change of the coordination geometry of the lanthanide centers.